Individualized antithrombotic therapy in high-risk cardiovascular patients. (25th May 2018) - Tegtmeyer, Roland; Borst, Oliver; Gawaz, Meinrad; Rath, Dominik
Recent guidelines suggest dual antiplatelet therapy (DAPT) after 'drug-eluting' stent (DES) implantation for 6 months in stable patients and for 12 months in patients after acute coronary syndrome. Serious complications after stent implantation include stent thrombosis, recurrent myocardial infarction, ischemic stroke, cardiovascular death and bleeding. These complications also occur beyond 1 year after coronary intervention. Thus, it is important to consider whether a prolonged DAPT (>12 months after percutaneous coronary intervention) is of benefit to lower thrombo-ischemic events in high-risk patients. This review addresses the results of recent randomized clinical studies (DAPT, ITALIC, OPTIDUAL and PEGASUS) and meta-analyses to support the author's view of which patient collectives might benefit from prolonged DAPT.